Reconstruction of the Principle of Proportionality in Contract Law within the Palm Oil Plantation Sector - Sayuti, Ageng Triganda; Nurdin, Zefrizal; Rembrandt, Rembrandt; Syofiarti, Syofiarti (Faculty of Law, Universitas Negeri Semarang, 2026)
This paper investigates the urgent need to reconstruct the principle of proportionality within contracts for palm oil partnerships, where structural power imbalances, information asymmetry, opaque financing arrangements, and unilateral sanction mechanisms systematically disadvantage plasma smallholders. The study aims to identify the fundamental factors that hinder the effective application of proportionality in oil palm partnership and to formulate an operational framework capable of ensuring contractual justice within highly asymmetric agribusiness relationships. Employing a normative juridical method complemented by conceptual, comparative, and socio-legal approaches, this research analyses Indonesian contract law, institutional practices, and international regulatory models drawn from Malaysia, Thailand, and India. The findings reveal that the proportionality principle in Indonesia remains largely abstract and lacks enforceable parameters, enabling exploitative contractual clauses such as undisclosed deductions, disproportionate risk distribution, and one-sided penalties to persist in nucleus plasma schemes. Comparative insights demonstrate that proportionality can be translated into practice through mandatory disclosure obligations, standardized minimum clauses, equitable risk-sharing mechanisms, contract registration, and accessible local dispute-resolution systems. The principal novelty of this study lies in proposing a three-pillar operational model of proportionality substantive, procedural, and sanction-based integrated with institutional governance reforms and community empowerment strategies. The paper concludes that reconstructing proportionality requires both normative refinement and structural intervention across negotiation processes, corporate procurement practices, evidentiary mechanisms, and state oversight. This integrated framework provides a concrete basis for embedding substantive justice within palm oil agreements and strengthening legal protection for structurally weaker parties.